Zum Umgang mit Sakralität in einer traditionell geprägten Gesellschaft (Anhand ethnographischer Materialien aus Georgien) - Khutsishvili, Ketevan (Georgica, 2016)
The article analyses ethnographic data gathered from various regions of Georgia, demonstrating that dreams are viewed by individuals of different ages, genders, educational backgrounds, and professions as a means of communication with deities (i.e., the sacred world), the deceased (i.e., the afterlife), the past and the future (i.e., across time), and space. A dream can serve as the cause, pretext, or justification for a certain form of social organisation. Based on this communicative function attributed to dreams, people construct social ties. Operating through imagery and symbols that are both deeply individual to each person and general, dreams reflect cultural roots alongside situational contexts and conventions. Collective experience is embedded in these symbols, providing crucial insights into a society’s worldview, beliefs, perceptions, and internal relationships.